Prevalence of Klebsiella oxytoca in milk samples of metropolitan city Kolkata: A study - Saini, Meenu; Raj, Atul; Bhattacharyya, Sayan; Banik, Amit; Chattopadhyay, Utpal Kumar (Eastern Journal of Medical Sciences, 2020)
Background: Klebsiella oxytoca is an emerging pathogen and can cause a plethora of infections in man. It is often found in food. Objective: The objective of the study was to assess the prevalence of K. oxytoca in milk samples and study their antibiogram. Methods: A total of 100 milk samples collected from various sources were cultured. Results: A total of seven isolates of K. oxytoca were found in 100 samples and none were multidrug-resistant. Isolates were uniformly susceptible to ofloxacin and chloramphenicol. They coexisted with other coliforms in some of these samples. Conclusion: Raw milk is an important source of K. oxytoca which can be pathogenic by oral route.